Factors influencing teachers’ self-efficacy at a rural school during the COVID-19 era - Kwanele Masondo (International Journal of Studies in Psychology)
This study explored factors influencing teachers’ self-efficacy and how teachers’ self-efficacy could be improved in the workplace during the COVID-19 pandemic. This study employed a qualitative approach to show how the worldwide COVID-19 pandemic affected classrooms in a rural school in South Africa. People had to adapt to a new way of life to prevent the spread of the disease. COVID-19 created enormous challenges and changes in educational systems. Over and above the changes, the rural schools suffer from issues inherited from the disadvantages of apartheid marginalisation. Teachers face many challenges, increasing their stress levels and forcing them into early retirement. Some teachers remain positive, committed, and inspired despite the challenges. These positive and enabling factors influence these teachers to work harder and believe they can overcome obstacles. Finally, this study will aid in exploring the enabling factors and the depth of their influence.